2019
DOI: 10.5267/j.msl.2019.6.026
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between green HRM and green management towards fostering green values

Abstract: The present study attempted to understand the nexus between Green HRM, Green Management towards explaining individual Green values. The study also attempted to test the moderation of green management on the relationship between Green HRM and individual Green values. A large private distribution business in Bahrain was chosen for the present study based on the recent initiatives towards green practices across the major work prospects. Results of the structural equation modelling from the non-managerial employee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 26 publications
4
30
0
4
Order By: Relevance
“…The present study suggests that part-time students are more confident and more determined to succeed compared to full-time students. These results support those of previous literature, where the impact of study mode on accounting students' self-efficacy was analysed (Jackson, 2013;Alzgool, 2019;Muhammad, Saoula, Issa & Ahmed, 2019). In this study sample, the percentage of part-time students who secured employment was 37.5% (9 out of 24 students who studied in part-time mode), compared to 14.6% (45 out of 308) for full-time students.…”
Section: Self-efficacy Factors and Study Modesupporting
confidence: 91%
“…The present study suggests that part-time students are more confident and more determined to succeed compared to full-time students. These results support those of previous literature, where the impact of study mode on accounting students' self-efficacy was analysed (Jackson, 2013;Alzgool, 2019;Muhammad, Saoula, Issa & Ahmed, 2019). In this study sample, the percentage of part-time students who secured employment was 37.5% (9 out of 24 students who studied in part-time mode), compared to 14.6% (45 out of 308) for full-time students.…”
Section: Self-efficacy Factors and Study Modesupporting
confidence: 91%
“…Also, the aspect of Islamic banking litigations is yet to be covered by BOFIA. In Malaysia, when the courts are to decide Shariah issues on Islamic banking, they are required to refer to the SAC rulings or resolutions to avoid counter-Shariah judgements (Mohamed et al, 2015;Khalid, Islam & Ahmed, 2019;Alzgool, 2019) Hence, to complement the above discussion, it can be argued that some BOFIA provisions are directly or indirectly contradicting Shariah standard, or may pose challenges for Islamic banking smooth operations. This simply means that the majority of the provisions are not in support of the establishment and expansion of Islamic banking in Nigeria.…”
Section: Loopholes In Islamic Banking Primary Legislation In Nigeria: Bofia (1991) In Focusmentioning
confidence: 99%
“…In recent years, there has been a great deal of interest in employee engagement. Many have claimed that employee engagement predicts employee outcomes, organizational success, and financial performance (e.g., total shareholder return) (Alzgool, 2019;Turner, 2019;Zhou et al, 2018). At the same time, it has been reported that employee engagement is on the decline, and there is a deepening disengagement among employees today (Turner, 2019;Zhou et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%